HBot: speaker bot educacional baseado em inteligência artificial para o auxílio na realização de deveres de casa de alunos do ensino fundamental - Silva , Luiz Rodrigo Jardim da (Universidade do Vale do Rio dos Sinos, 2019)
The school of the future is a subject that is constantly discussed among educational managers and teachers. Among the questions that guide this theme, is the fact of how to adapt to technology implementation, since in Brazil we still suffer from structural problems, which has contributed, in a way, to the distance of students from the school environment. Technology is intrinsically related to this reality, because today's young people are surrounded by technological products. Their absence within the school, or even its misuse, can lead to disinterest in the development of extra-class work, as well as even contributing to school dropout. This paper aims to present a model aimed at the development of homework for students from elementary school. The model when implemented will result in a system based in Artificial Intelligence to help the teacher to propose a set of questions to be solved through a Smart Speaker, providing a reliable knowledge base.
Keywords: Tecnologia; Inteligência artificial; Escola; Deveres de casa; Smart speaker; Homeworks; Artificial intelligence